Two New Families of Floating FDNR Circuits. (31st August 2010) - Soliman, Ahmed M.; Saad, Ramy A.
Abstract : Two new configurations for realizing ideal floating frequency-dependent negative resistor elements (FDNR) are introduced. The proposed circuits are symmetrical and are realizable by four CCII or ICCII or a combination of both. Each configuration is realizable by eight different circuits. Simulation results are included to support the theory.